Treatment of chronic lateral ankle instability using the Broström-Gould procedure in athletes: long-term results - RUSSO, ADRIANO (Joints, 2016)
PURPOSE: this study was conducted to evaluate long-term results following treatment of chronic lateral ankle instability using the Broström-Gould technique in athletes. METHODS: eighteen athletes involved in competitive sports at different levels, who suffered from chronic lateral ankle instability, underwent Broström-Gould ligamentoplasty between 2000 and 2005. The results of the surgery were evaluated using the American Orthopaedic Foot and Ankle Society (AOFAS) scale. RESULTS: the results at 10–15 years of follow-up were excellent in 94.5% of these cases and good in the remaining 5.5%. An increase of 31.2 points in the AOFAS scale score was recorded at follow-up (with the score rising to 98.8, from 67.6 preoperatively). All the athletes returned to their respective sports at the same level as prior to the surgery. Imaging at long-term follow-up showed no signs of arthritic degeneration. CONCLUSIONS: the results of this study show that the Broström-Gould technique is an effective procedure for the treatment of chronic lateral ankle instability in the athlete, giving excellent long-term results. LEVEL OF EVIDENCE: therapeutic case series, level IV.